NON HALAL INCOME: CRITICAL OF ACCOUNTING TREATMENT, SOURCE AND UTILIZATION AT BANK ACEH SYARIAH - Indrayani; Lilik Purwanti (CV. Radja Publika, 2023)
The purpose of this study is to examine the sources of non-halal income and its usage in Aceh Sharia banking, as well as to critique the use of non-halal income sources. This research employs a qualitative method with a critical approach to the consistency of Sharia banking compliance with Islamic principles. The results show that Aceh Sharia Bank's use, measurement, presentation, and disclosure of financial information are in line with PSAK 101. Aceh Sharia Bank obtains non-halal income from placing funds in non-sharia banks and earning interest income that is used to fund social activities. This creates a paradox for sharia banks that encourage people to migrate to sharia banking, while their funds are mostly placed in non-sharia banks and used for public purposes that enhance the positive image of sharia banking.